Practical Aerobic Oxidation of Alcohols: A Ligand‐Enhanced 2, 2, 6, 6‐Tetramethylpiperidine‐1‐oxy/Manganese Nitrate Catalyst System. Issue 20 (7th September 2017) - Lagerblom, Kalle; Lagerspets, Emi; Keskiväli, Juha; Cook, Chris; Ekholm, Filip; Parviainen, Arno; Repo, Timo
Abstract: A highly efficient, ligand‐enhanced 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxy (TEMPO)/Mn(NO3 )2 catalyst system for the aerobic oxidation of alcohols is described. From the series of coordinating ligands studied herein, 2‐picolinic acid (PyCOOH) improves the catalytic activity of TEMPO/Mn(NO3 )2 remarkably. Under ambient air at room temperature in acetic acid, the ligand‐enhanced catalyst converts aliphatic and benzylic primary alcohols that bear various functional groups into their respective aldehydes with near quantitative conversions. The applicability of the catalyst for convenient preparative synthesis was demonstrated by conducting oxidations on a gram scale. A change of TEMPO to the sterically less demanding 9‐azabicyclo[3.3.1]nonane N ‐oxyl results in a Mn catalyst that is also able to oxidize secondary alcohols to ketones. Mechanistic studies showed that alcohols are oxidized by the oxoammonium cation derived from the nitroxyl radical. The active oxidant is regenerated by Mn(NO3 )2, and this process is greatly promoted by the coordination of PyCOOH to Mn. Abstract : Simply efficient : A highly active and selective catalyst for the aerobic oxidation of alcohols was developed. The method is based on a 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxy/Mn(NO3 )2 catalyst, the activity of which is increased significantly by the addition of 2‐picolinic acid as a coordinating ligand. The ligand‐enhanced system is used for the oxidation of various primary alcohols to aldehydes using ambient air as the oxidant.